T-bet+ B cells are activated by and control endogenous retroviruses through TLR-dependent mechanisms - Rauch, Eileen; Amendt, Timm; Lopez Krol, Aleksandra; Lang, Fabian B.; Linse, Vincent; Hohmann, Michelle; Keim, Ann Christin; Kreutzer, Susanne; Kawengian, Kevin; Buchholz, Malte; Duschner, Philipp; Grauer, Saskia; et al. (Nature Communications, 2024)
Endogenous retroviruses (ERVs) are an integral part of the mammalian genome. The role of immune control of ERVs in general is poorly defined as is their function as anti-cancer immune targets or drivers of autoimmune disease. Here, we generate mouse-strains where Moloney-Murine Leukemia Virus tagged with GFP (ERV-GFP) infected the mouse germline. This enables us to analyze the role of genetic, epigenetic and cell intrinsic restriction factors in ERV activation and control. We identify an autoreactive B cell response against the neo-self/ERV antigen GFP as a key mechanism of ERV control. Hallmarks of this response are spontaneous ERV-GFP+ germinal center formation, elevated serum IFN-γ levels and a dependency on Age-associated B cells (ABCs) a subclass of T-bet+ memory B cells. Impairment of IgM B cell receptor-signal in nucleic-acid sensing TLR-deficient mice contributes to defective ERV control. Although ERVs are a part of the genome they break immune tolerance, induce immune surveillance against ERV-derived self-antigens and shape the host immune response.
CRIS-Team Scopus Importer:2024-02-23